Efficacy of acupuncture in treating chemotherapy-related cognitive impairment in breast cancer patients: A systematic review and meta-analysis protocol - Lishi Liu; Zihan Meng; Jun Yan (PLoS ONE, 2025)
Background Chemotherapy-related cognitive impairment (CRCI) is a common adverse effect of chemotherapy in breast cancer patients, with a high incidence that significantly impacts treatment adherence and quality of life. Currently, there is no definitive and effective treatment for CRCI. Research indicates that acupuncture may serve as a promising intervention for CRCI. This study aims to assess the effectiveness of acupuncture in treating CRCI. Methods This study is guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols (PRISMA-P). From the time of database construction to October 2024, we will search seven literature databases, three clinical study registry databases, and three sources of gray literature. The restricted languages are English and Chinese. We will use the Participants-Interventions-Comparators-Outcome-Conclusion-Study Design (PICOS) criteria to identify included studies and the RoB2 tool to assess the quality of the included studies. Data synthesis and meta-analysis will be performed using RevMan 5.3. Discussion The results of this study will clarify the potential benefits of acupuncture in the treatment of CRCI and address existing disagreements about its efficacy. Furthermore, the findings will assist clinicians in making informed decisions regarding the treatment of CRCI. Trail registration PROSPERO registration number: CRD42024568093.